2002
DOI: 10.1073/pnas.222467299
|View full text |Cite
|
Sign up to set email alerts
|

KaiA-stimulated KaiC phosphorylation in circadian timing loops in cyanobacteria

Abstract: Cyanobacterial clock proteins KaiA and KaiC are proposed as positive and negative regulators in the autoregulatory circadian kaiBC expression, respectively. Here, we show that activation of kaiBC expression by kaiA requires KaiC, suggesting a positive feedback control in the cyanobacterial clockwork. We found that robust circadian phosphorylation of KaiC. KaiA was essential for in vivo KaiC phosphorylation and activated in vitro KaiC autophosphorylation. These effects of KaiA were attenuated by the kaiA2 long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
377
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(396 citation statements)
references
References 17 publications
19
377
0
Order By: Relevance
“…Furthermore, our previous results from a radioactive phosphate uptake assay showed that a small amount of phosphate was incorporated into KaiC even when KaiA was not included in the reaction (Iwasaki et al 2002;Kitayama et al 2003). We also confirmed that the ratio of phosphorylated serine and threonine was not altered by the presence of KaiA, whereas KaiA increased the overall level of phosphorylation at both residues (Iwasaki et al 2002).…”
Section: A Sequential Program Of Kaic Phosphorylationsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, our previous results from a radioactive phosphate uptake assay showed that a small amount of phosphate was incorporated into KaiC even when KaiA was not included in the reaction (Iwasaki et al 2002;Kitayama et al 2003). We also confirmed that the ratio of phosphorylated serine and threonine was not altered by the presence of KaiA, whereas KaiA increased the overall level of phosphorylation at both residues (Iwasaki et al 2002).…”
Section: A Sequential Program Of Kaic Phosphorylationsupporting
confidence: 84%
“…Therefore, KaiC is the primary determinant of the circadian period of cyanobacteria. One candidate for the molecular process that determines the circadian period is the phosphorylation of KaiC, which exhibits a robust circadian rhythm in its phosphorylation level in vivo (Iwasaki et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In one of the more remarkable discoveries in the field in recent years, it was shown that a circadian oscillation of KaiC phosphorylation could be reconstituted in vitro with the purified KaiA, KaiB, and KaiC proteins . KaiA enhances KaiC autophosphorylation, while KaiB antagonizes the effects of KaiA (Iwasaki et al, 2002;Williams et al, 2002;Kitayama et al, 2003;Xu et al, 2003).…”
Section: The Circadian Clock System In Cyanobacteriamentioning
confidence: 99%
“…The proteins encoded by these genes interact with one another (Iwasaki et al, 1999;Taniguchi et al, 2001;Xu et al, 1999) to form large complexes in vivo with KaiC as the core (Kageyama et al, 2003). KaiC exists in both phosphorylated and nonphosphorylated forms in vivo, and its phosphorylation status is correlated with clock speed (Nishiwaki et al, 2000;Iwasaki et al, 2002;Xu et al, 2003;Johnson, 2004). In one of the more remarkable discoveries in the field in recent years, it was shown that a circadian oscillation of KaiC phosphorylation could be reconstituted in vitro with the purified KaiA, KaiB, and KaiC proteins .…”
Section: The Circadian Clock System In Cyanobacteriamentioning
confidence: 99%
See 1 more Smart Citation